IMPLEMENTASI WAKAF TUNAI DALAM PEREKONOMIAN DAN PENGEMBANGAN INFRASTRUKTUR - Rahmasari, Dewi; Firdaus, Fira Fara; Rahmawati, Lilik; Nadia, Nada El; Hadi, Nurrohman (Program Studi Ekonomi Islam FEI UNIDA Bogor, 2020)
This study aims to determine the implementation of cash waqf in the economy and infrastructure development. How to manage cash waqf so that they can advance and develop the economy. And discuss what potential is produced. Along with the development of the waqf era has become the culture of the wider community that is applied until now, but most of them only apply the commonly done as endowments. The existence of this journal aims to increase understanding of cash waqf which is a driving force for the economy and infrastructure.